2011
DOI: 10.1093/nar/gkr1002
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-free cellular uptake and the gene-silencing activity of the lipophilic siRNAs is strongly affected by the length of the linker between siRNA and lipophilic group

Abstract: The conjugation of siRNA to molecules, which can be internalized into the cell via natural transport mechanisms, can result in the enhancement of siRNA cellular uptake. Herein, the carrier-free cellular uptake of nuclease-resistant anti-MDR1 siRNA equipped with lipophilic residues (cholesterol, lithocholic acid, oleyl alcohol and litocholic acid oleylamide) attached to the 5′-end of the sense strand via oligomethylene linker of various length was investigated. A convenient combination of H-phosphonate and phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 65 publications
3
91
0
2
Order By: Relevance
“…Likewise, the transport of ODNs first to and then out of the nucleus has already been reported [63]. These observations are also in agreement with the results achieved by other authors who reported that the efficiency of cellular accumulation of lipophilic siRNAs was dependent upon the type of cell line tested [29].…”
Section: Cell Cytotoxicity Cellular Binding Uptake and Localizationsupporting
confidence: 89%
See 1 more Smart Citation
“…Likewise, the transport of ODNs first to and then out of the nucleus has already been reported [63]. These observations are also in agreement with the results achieved by other authors who reported that the efficiency of cellular accumulation of lipophilic siRNAs was dependent upon the type of cell line tested [29].…”
Section: Cell Cytotoxicity Cellular Binding Uptake and Localizationsupporting
confidence: 89%
“…Cells were seeded at 1.25 × 10 5 cells/well in 24-well plates and incubated overnight in appropriate growth medium. Then cells were incubated in the presence of Cy5-or Alexa 488-labeled LOCs, ODN and ODN-lipoplexes at 37°C for 4 h. All these experiments were performed using OptiMEM because the transfection efficiency of several standard transfection reagents is reduced in the presence of serum [26][27][28][29][30]. After incubation, cells were completely dissociated in 0.5% Trypsin-EDTA (Invitrogen).…”
Section: Cellular Binding/uptake Studies By Flow Cytometrymentioning
confidence: 99%
“…Three different anticancer siRNAs and one scrambled siRNA were chosen from previously published results (Bellon, 2001;Braicu et al, 2013;Guoan et al, 2010;Jagani et al, 2011Jagani et al, , 2013Petrova et al, 2012). The sequences of the siRNAs are presented in the supporting information…”
Section: Sirnamentioning
confidence: 99%
“…Cholesterol-siRNA conjugates can form particles with lipoproteins in blood circulation, which increases circulation time and promotes uptake into the hepatocytes via lipoprotein receptors [39]. The lipid-siRNA conjugates have been further optimized by using new lipids such as α-tocopherol [40] and by controlling the length of the linker between siRNA and lipid [41]. …”
Section: Molecular Conjugatesmentioning
confidence: 99%